Proceedings of the 4th International Conference on Collaborative Virtual Environments 2002
DOI: 10.1145/571878.571882
|View full text |Cite
|
Sign up to set email alerts
|

Culture formation and its issues in personal agent-oriented virtual society

Abstract: In recent years, the combination of communication networks and computer technologies have made it possible to create a cyberspace on the Internet. Recently, several 3D shared virtual spaces and worlds have been developed in which users can share the same experience in a shared virtual environment [1] [10]. The next important step is to extend these environments into a "virtual society."To realize a virtual society, it is important to obtain a large number of users in a virtual world and evaluate various issues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…We used statistical methods to evaluate reasons for users to access PAWˆ2 and found that the main factor was the use of a personal agent (Matsuda & Yajima, 2000), which received very high rankings. We also observed various interesting cultural phenomena emerging in PAWˆ2 (Matsuda, Miyake, & Kawai, 2002). For example, several distinct communities were formed in PAWˆ2 and established rules for living in that virtual society.…”
Section: Introductionmentioning
confidence: 68%
“…We used statistical methods to evaluate reasons for users to access PAWˆ2 and found that the main factor was the use of a personal agent (Matsuda & Yajima, 2000), which received very high rankings. We also observed various interesting cultural phenomena emerging in PAWˆ2 (Matsuda, Miyake, & Kawai, 2002). For example, several distinct communities were formed in PAWˆ2 and established rules for living in that virtual society.…”
Section: Introductionmentioning
confidence: 68%
“…Matsuda et al developed a virtual society, called PAW, and carried out an open experiment (Matsuda 2002). From the result of the open experiment, they presented the user's profile, the effect of an event, the feature of communities, and the communication tools for using all these together.…”
Section: 2mentioning
confidence: 99%
“…Shared virtual environments with ECAs are becoming increasingly common (for a large-scale commercial example, see [11]), and we (and others-see [19]) see this as an important application area for ECAs. There is already evidence that nonembodied software agents that communicate with human users in text-chat virtual worlds are engaging [2].…”
Section: Introductionmentioning
confidence: 99%